Management of nutrient interactions in agriculture - Tandon, H. L. S. (Hari Lal Singh), 1943-; Fertiliser Development and Consultation Organisation (New Delhi, India : Fertiliser Development and Consultation Organisation, 1992)
Eight articles on balanced and efficient use of fertilizers.
Includes bibliographical references.
Keywords: Crops -- Nutrition -- India; Fertilizers -- India; Crops and soils -- India